2005
DOI: 10.1007/s00330-005-2855-1
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal glands in beta-thalassemia major: magnetic resonance (MR) imaging features and correlation with iron stores

Abstract: This study aimed at describing the magnetic resonance (MR) imaging features of the adrenal glands in beta-thalassemic patients and at investigating the relation between adrenal and hepatic siderosis. Adrenal signal intensity (SI) was retrospectively assessed on abdominal MR studies of 35 patients with beta-thalassemia major undergoing quantification of hepatic siderosis and 12 healthy controls, using T1-(120/4/90), intermediate-(120/4/20), and T2*-(120/15/20) weighted GRE sequences. Adrenal SI was graded as gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 35 publications
(88 reference statements)
3
30
0
1
Order By: Relevance
“…Imaging studies using MR have frequently identified adrenal hypointensity without alteration of morphology in thalassaemia patients and verified autopsy findings of correlation between adrenal iron and liver iron [94]. However, despite high sensitivity, histology still remains the gold standard for diagnosis of iron deposition.…”
mentioning
confidence: 85%
“…Imaging studies using MR have frequently identified adrenal hypointensity without alteration of morphology in thalassaemia patients and verified autopsy findings of correlation between adrenal iron and liver iron [94]. However, despite high sensitivity, histology still remains the gold standard for diagnosis of iron deposition.…”
mentioning
confidence: 85%
“…Target Organ-Although MRI is most often used to estimate cardiac and hepatic iron, MRI can also been used to characterize tissue iron deposits in the brain, pituitary gland, bone marrow, kidney and pancreas (36)(37)(38)(39)(40)(41)(42). These approaches observe the same physical principles as cardiac and hepatic iron imaging but present different imaging challenges.…”
Section: Choice Of Field Strength-mostmentioning
confidence: 99%
“…In contrast, splenic iron deposits are quite large and spin-echo (R2) techniques will not yield accurate iron estimates in this organ. The merits and limitations of these other techniques are beyond the scope of this manuscript, but several key references are included for interested readers (36)(37)(38)(39)(40)(41)(42).…”
Section: Choice Of Field Strength-mostmentioning
confidence: 99%
“…MRI has also been used to characterize tissue iron deposits in the brain, pituitary gland, bone marrow, kidney and pancreas [65][66][67][68][69][70][71]. Although less well validated and clinically exploited, these approaches are likely to become increasingly important in the assessment of transfusional iron overload.…”
Section: Other Target Organ Assessmentsmentioning
confidence: 99%